Quantitative and qualitative sex difference in habenula-induced inhibition of midbrain dopamine neurons in the rat - Bell, Dana; Waldron, Vaughn J.; Brown, P. Leon (Frontiers in Behavioral Neuroscience, 2023)
Introduction: Clinically relevant sex differences have been noted in a number of affective, behavioral, cognitive, and neurological health disorders. Midbrain dopamine neurons are implicated in several of these same disorders and consequently are under investigation for their potential role in the manifestation of these sex differences. The lateral habenula exerts significant inhibitory control over dopamine neuronal firing, yet little is known about sex differences in this particular neurocircuit.We performed in vivo, single unit, extracellular recordings of dopamine neurons in female and male anesthetized rats in response to single pulse stimulation of the lateral habenula. In addition, we assessed baseline firing properties of lateral habenula neurons and, by immunochemical means, assessed the distribution of estrogen receptor alpha cells in the lateral habenula.Results: Habenula-induced inhibition of dopamine neuronal firing is reduced in female rats relative to male rats. In addition, male rats had a higher prevalence of rebound excitation. Furthermore, the firing pattern of lateral habenula neurons was more regularless variable in female rats, and that female rats had a higher density of estrogen receptor alpha positive cells in the lateral habenula.Discussion: We found that the dopamine neuronal response to habenular stimulation is both qualitatively and quantitatively different in female and male rats. These novel findings together with reports in the contemporary literature lead us to posit that the sex difference in dopamine inhibition seen here relate to differential firing properties of lateral habenula neurons resulting from the presence of sex hormones. Further work is needed to test this hypothesis, which may have implications for understanding the etiology of several mental health disorders including depression, schizophrenia, and addiction.